L’intervention sociale auprès des groupes en région ressource : regard sur les expériences d’intervention vécues par les intervenantes issues du travail social - Labra, Oscar; Castro, Carol; Grenier, Stéphane (Canadian Social Work Review, 2024)
Nous en connaissons peu sur la pratique d’intervention de groupe en région, ce qui ouvre un champ de questions qui dépassent de loin la simple description des conditions de travail en intervention. Ce travail souhaite valoriser et rendre « visible » la pratique d’intervention de groupe des professionnelles issues du travail social, dans un contexte québécois, et plus spécifiquement dans un environnement de région ressource, environnement qui pose des défis et des enjeux importants reliés à ce mode d’intervention. À travers une recherche qualitative et un processus de théorisation ancrée, ce mode d’intervention a été exploré auprès de 10 intervenantes. Les principaux résultats nous permettent d’identifier les spécificités régionales de l’intervention de groupe, telles qu’une pratique destinée fondamentalement aux femmes avec des approches choisies pour l’intervention, la confidentialité et la protection de la vie privée des participantes du groupe, le manque de transport en commun, et une pratique de groupe plus présente dans le milieu communautaire. , We know little about the practice of group intervention in remote areas, which leads to an array of questions that go far beyond the mere description of working conditions in this context of practice. This article aims to acknowledge and increase visibility of social work with groups in Quebec, most specifically in remote regions where mostly female social work professionals practice this type of intervention, an environment that poses important challenges related to this type of practice. Through qualitative research and a process of grounded theorizing, this type of intervention was explored using feedback from 10 female participants (social workers). The main results highlight regional specificities, such as a practice fundamentally aimed at women, confidentiality and privacy of group participants, the lack of public transportation, and a group practice more present in the community setting

Seniors Who Experienced the Lac-Mégantic Train Derailment Tragedy: What Are the Consequences on Physical and Mental Health? - Maltais, Danielle; Tremblay, Anne-Julie; Labra, Oscar; Fortin, Geneviève; Généreux, Mélissa; Roy, Mathieu; Lansard, Anne-Lise (Gerontology and Geriatric Medicine, 2019)
Introduction: In July 2013, a train derailment caused the death of 47 people and destroyed the downtown area in the city of Lac-Mégantic (Quebec, Canada). This tragedy had several impacts on this small community. Method: Three years after this disaster, we used a representative population-based survey conducted among 800 adults (including 265 seniors aged 65 or above) to assess the physical and mental health of seniors. Results: Several differences were observed in seniors’ physical and mental health based on their level of exposure to the tragedy. Nearly half of seniors highly exposed to the train derailment (41.7%) believe that their health has deteriorated in the past 3 years. The majority of seniors highly exposed to the train derailment (68.7%) also show symptoms of posttraumatic stress disorders. Seniors highly or moderately exposed to the tragedy were also more likely to have found positive changes in their personal and social life as compared with nonexposed seniors. Discussion: A technological disaster such as a train derailment still had negative impacts on seniors’ physical and mental health 3 years later. Conclusion: Public health authorities must tailor prevention and promotion programs to restore health and well-being in this population.
Keywords: Généreux_Mélissa